(untitled) (Journal of Plant Disease Sciences, 2025)
Chilli (Capsicum annuum L.) is one of the most widely grown vegetable crops and is extensively used as a spice crop throughout the world. The chilli crop is affected by several diseases such as damping-off, wilt, anthracnose, die-back, root rot and bacterial wilt. Among the fungal diseases, damping-off caused by Pythium aphanidermatum (Edson) Fitzp. in nurseries is a major constraint in chilli production, resulting in up to 62% seedling mortality and accounting for nearly 90% plant death either as pre- or post-emergence damping-off under nursery conditions. Traditionally, the disease is managed using synthetic fungicides such as metalaxyl and carbendazim; however, their repeated use often leads to phytotoxicity and environmental concerns. This has created a need to evaluate newer fungicide formulations and eco-friendly alternatives for effective disease management. The present study was undertaken to evaluate the efficacy of newer fungicides and biocontrol agents against chilli damping-off disease. The results revealed that Metalaxyl-M 4% + Mancozeb 64% WP, Trifloxystrobin 25% + Tebuconazole 50% WG, and Mancozeb 64% + Cymoxanil 8% WP were the most effective treatments, showing 100% inhibition of the pathogen at the recommended concentration. Among the biocontrol agents tested, Bacillus subtilis and Pseudomonas fluorescens showed the highest antagonistic activity against the pathogen, recording 71.30% and 68.52% inhibition, respectively. The study indicates that newer fungicide combinations and selected biocontrol agents can be effectively utilized for managing damping-off disease of chilli in an eco-friendly and sustainable manner.